2021
DOI: 10.1101/2021.06.25.21259158
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Utility of family history in disease prediction in the era of polygenic scores

Abstract: Clinicians have historically used family history and other risk prediction algorithms to guide patient care and preventive treatment such as statin therapeutics for coronary artery disease. As polygenic scores move towards clinical use, we have begun to consider the interplay of these scores with other predictors for optimal second generation risk prediction. Here, we assess the use of family history and polygenic scores as independent predictors of coronary artery disease and type 2 diabetes. We highlight con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…2 Lastly, our models were based on only a single PGS, although the performance of several different genome-wide PGSs (ie, those derived from statistical methods, such as metaGRS, LDpred, or PRS-CS) have shown to be nearly equivalent in CAD prediction. 26…”
Section: Discussionmentioning
confidence: 99%
“…2 Lastly, our models were based on only a single PGS, although the performance of several different genome-wide PGSs (ie, those derived from statistical methods, such as metaGRS, LDpred, or PRS-CS) have shown to be nearly equivalent in CAD prediction. 26…”
Section: Discussionmentioning
confidence: 99%
“…One way to mitigate against including imprecise risk factors in risk prediction is to plan during the study design stage, and collect the correct covariates required for traditional statistical models, such as QRISK3, in large scale cohort studies. As suggested by Wolford et al 2021, biobanks should collect high quality family history risk factors for use in future prediction models. During our preliminary work on an independent external validation of QRISK3 using UK Biobank data, we found that UK Biobank lacks information on the age at which family members were diagnosed with coronary heart disease (a requirement for the QRISK3 model), as shown in Table 1.…”
Section: Collecting the Most Appropriate Risk Factorsmentioning
confidence: 99%